Web Design Requirements for Improved Web Accessibility for the Blind - Baguma, Rehema; Lubega, Jude T. (Springer, Berlin, Heidelberg, 2008)
Considerable research has been done on how to make e-learning systems accessible. But Learners in electronic and hybrid learning environments utilize many Web based systems beyond what the instructor and institution provides and can control such as search engines, news portals and research databases. This paper presents Web design requirements that can improve the accessibility of such websites for PWDs particularly the blind. The requirements were derived from both theoretical and quantitative data gathered from both literature and a case study. It was observed that graphical user interfaces, non-linear navigation, forms, tables, images, lack of key board support, nonstandard document formats and acronyms and abbreviations hinder Web accessibility for the blind. Therefore in order to improve Web accessibility for the blind, the following requirements were suggested; a text only version of the website or a combination of design considerations namely: text alternatives for visual elements, meaningful content structure in the source code, skip navigation link(s), orientation during navigation, ensure (tables, frames and forms) are accessible if any is used, test the website with keyboard only access, use or convert documents into standard formats and expand abbreviations and acronyms the first time they appear on a page. Meeting the given requirements in the Web development process improves Web accessibility for all blind Web users including those engaged in hybrid learning.
Keywords: Web Accessibility; Requirements; Blind; Hybrid Learning; E-learning